Elevated water lead levels in schools using water from on-site wells - Scott Latham; Jennifer L. Jennings (IWA Publishing, 2022)
Only 8% of US public schools operate their own community water systems, and thus are subject to the federal Lead and Copper Rule's regulation of water lead levels (WLLs). To date, the absence of parallel water testing data for all other schools has prevented the comparison of WLLs with schools that do not face federal regulation. This study compiled and analyzed newly available school-level WLL data that included water source (on-site well water or public utility) and pipe material data for public schools in New York State located outside of New York City. Despite direct federal regulation, schools that used water from on-site wells had a substantially higher percentage of water fixtures with elevated WLLs. Schools that used both on-site well water and iron pipes in their water distribution system had the highest percentage of elevated fixtures. Variation in water treatment practices was identified as a potential contributing mechanism, as schools that used on-site well water were less likely to implement corrosion control. The study concluded that information about water source and premise plumbing material may be useful to policymakers targeting schools for testing and remediation. HIGHLIGHTS Examined the prevalence of fixtures with elevated water lead levels in NY public schools outside of New York City.; Schools that sourced water from on-site wells had nearly twice as many elevated fixtures as schools that used utility water.; Schools with wells and iron pipes in their systems had the highest percentage of elevated fixtures.; Schools that used wells were less likely to treat water for corrosion control than a comparison sample of community water systems.;